Composition‐Graded Cesium Lead Halide Perovskite Nanowires with Tunable Dual‐Color Lasing Performance. Issue 27 (21st May 2018) - Huang, Ling; Gao, Qinggang; Sun, Ling‐Dong; Dong, Hao; Shi, Shuo; Cai, Tong; Liao, Qing; Yan, Chun‐Hua
Abstract: Cesium lead halide (CsPbX3 ) perovskite has emerged as a promising low‐threshold multicolor laser material; however, realizing wavelength‐tunable lasing output from a single CsPbX3 nanostructure is still constrained by integrating different composition. Here, the direct synthesis of composition‐graded CsPbBr x I3− x nanowires (NWs) is reported through vapor‐phase epitaxial growth on mica. The graded composition along the NW, with an increased Br/I from the center to the ends, comes from desynchronized deposition of cesium lead halides and temperature‐controlled anion‐exchange reaction. The graded composition results in varied bandgaps along the NW, which induce a blueshifted emission from the center to the ends. As an efficient gain media, the nanowire exerts position‐dependent lasing performance, with a different color at the ends and center respectively above the threshold. Meanwhile, dual‐color lasing with a wavelength separation of 35 nm is activated simultaneously at a site with an intermediate composition. This position‐dependent dual‐color lasing from a single nanowire makes these metal halide perovskites promising for applications in nanoscale optical devices. Abstract : Composition‐graded CsPbBr x I3 − x nanowires resulting from desynchronized deposition and anion exchange are efficiently synthesized via vapor‐phase growth. The graded Br/I along the nanowire endows it with tunable emission. Position‐dependent lasing with different colors from the ends and center is detected. Dual‐color lasing is activated simutaneously from the site with an intermediate composition to that of the ends and center.